Embodied Prevention - Kempermann, Gerd (Frontiers in Psychology, 2022)
Evidence-based recommendations for lifestyles to promote healthy cognitive aging (exercise, education, non-smoking, balanced diet, etc.) root in reductionistic studies of mostly physical measurable factors with large effect sizes. In contrast, most people consider factors like autonomy, purpose, social participation and engagement, etc., as central to a high quality of life in old age. Evidence for a direct causal impact of these factors on healthy cognitive aging is still limited, albeit not absent. Ultimately, however, individual lifestyle is a complex composite of variables relating to both body and mind as well as to receiving input and generating output. The physical interventions are tied to the more subjective and mind-related aspects of lifestyle and well-being in the idea of the ‘embodied mind,’ which states that the mind is shaped by and requires the body. The causality is reciprocal and the process is dynamic, critically requiring movement: the ‘embodied mind’ is a ‘embodied mind in motion’. Hiking, playing musical instruments, dancing and yoga are examples of body-mind activities that assign depth, purpose, meaning, social embedding, etc. to long-term beneficial physical ‘activities’ and increase quality of life not only as delayed gratification. The present motivational power of embodied activities allows benefiting from the side-effects of late-life resilience. The concept offers an access point for unraveling the mechanistic complexity of lifestyle-based prevention, including their (neuro-) biological foundations.